Costs and benefits of using social learning games to support Indian communities in better managing their dams - Falk, Thomas; Steimanis, Ivo; Bartels, Lara; Duche, Vishwambhar; Vollan, Björn; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2025)
India's water systems are under increasing pressure from widespread over-exploitation by agriculture, which consumes 80% of the country's fresh water. Dams, reservoirs, and other water harvesting structures constructed in rural communities can provide supplementary irrigation, especially during increasingly frequent dry spells, and reduce flood risks. In addition, these structures provide water for livestock and domestic purposes and support managed fisheries.